Pengaruh Profitabilitas, Pertumbuhan Perusahaan, Ukuran Perusahaan, dan Struktur Modal terhadap Keputusan Sektor Industri Basic materials Tahun 2020-2024 - Sakina Fitri Syahwa; Suhardi; Rita Deseria; Muhammad Raffi Uz-Zaky (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The disourse on strengthening the national manufacturing sector through the downstream industry program faces real challenges, including the decline in commodity prices that decrease firm profits, and weakening value of the major shares reflects the decline in investor perceptions of firm value. This research aims to review the effect of profitability, firm growth, firm size, and capital structure on investment decision, and explore the possible absence of influence of these variables in basic materials sector in 2020-2024. This research is quantitative using panel data regression analysis of 110 observation from 23 sample firm, with best estimation model identified as the Fixed Effect Model (FEM) and processed using E-views 12. The result showed that partially, profitability, and capital structure had no significant effect on investment decision. In contrast, firm growth has a significant efffect with a negative direction, so did firm size has a positive significant effect. Simultaneously, these four variables have significant effect on investment decision with the coefficient of determination indicating that the ability to explain in this model is powerful. Implication of this research is importance to evaluate all of internal factors that affect investment decision further in order to be able to realize the discourse of industrial downstreaming in the manufacturing sector.